High-grade Atrioventricular Block Due to Lacosamide and Tizanidine Combination Therapy for Epilepsy and Multiple Sclerosis - Kılıç, Sinem; Canpolat, Uğur (Acta Medica, 2022)
Drug-induced atrioventricular (AV) block can be caused by cardiac and non-cardiac medications. The clinical condition may be temporary, persistent, or recurrent. However, there is no standard approach for management and follow-up of patients with drug-induced AV block. Herein, we presented a patient with the diagnosis of epilepsy and multiple sclerosis who admitted to emergency room with epileptic seizure. Temporary advanced AV block was observed on admission and during in-hospital follow-up which was thought to be caused by lacosamide and tizanidine medications and improved after drug discontinuation.